The Importance of Changing Community Attitude in Increasing Switching Decision to Public Transportation: A Case Study of Denpasar City Community - Ni Putu Cempaka Dharmadewi Atmaja; I Gusti Agung Ngurah Gede Eka Teja Kusuma; I Made Dauh Wijana; Putu Anom Wisnu Wisnawa; I Gede Agus Sentana Widana yasa (AIBPM Publisher, 2025)
Traffic congestion is a very important thing for the Denpasar City government to handle at this time. One of the Denpasar city government's efforts to reduce speed is by introducing public transportation to the people of Denpasar City and its surroundings. However, public interest in public transportation is not very high. It is very important to carry out research on people's attitudes and behavior to be able to switch to public transportation. The aim of this research is to determine the role of attitudes in the influence of service quality on the decision of the people of Denpasar City to switch to public transportation. The research method uses path analysis with a sample size of 130 respondents. The research results state that service quality and attitude have a positive influence on the decision to switch to public transportation. This research also states that attitude can partially mediate the influence of service quality on the decision to switch to public transportation. The implication of the research is that the Denpasar city government should be able to improve public transportation services to the community so that it can increase the positive attitude of the community to switch to public transportation.